Studi Pemikiran Hasbi Ash-Shiddiqie Sebagai Tokoh Sentral Tafsir Keindonesiaan (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
Teungku Muhammad Hasbi Ash-Shiddiqi was Muhammad Hasbi, he was born in Lhokseumawe, North Aceh on 10 March 1904 and died in Jakarta on 9 December 1975. As an Nusantara exegetes, HASBI presents its interpretation in the context of Indonesia. The interpretation certainly cannot be separated from its scientific discipline and culture of Indonesian society. To realize the fikih of Indonesian personality, Hasbi departed from the understanding that the jurisprudence is a living and ununiversal organism. One example of HASBI interpretation is about Friday prayers. Hasbi said that on the day of the Jumát there is no prayer of four rak'ahs of Dhuhr. Therefore. Anyone who can not or does not have time to follow the Friday prayers in congregation in the mosque still have to work Friday prayers either together or alone. According to Hasbi, there was no Zuhr prayer during Friday. Berjemaah and the preaching does not include the pillars or the legitimate requirements of the Friday.